2017
DOI: 10.1109/tii.2016.2641472
|View full text |Cite
|
Sign up to set email alerts
|

Defect Detection in SEM Images of Nanofibrous Materials

Abstract: Nanoproducts represent a potential growing sector and nanofibrous materials are widely requested in industrial, medical, and environmental applications. Unfortunately, the production processes at the nanoscale are difficult to control and nanoproducts often exhibit localized defects that impair their functional properties. Therefore, defect detection is a particularly important feature in smart-manufacturing systems to raise alerts as soon as defects exceed a given tolerance level and to design production proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 57 publications
1
81
0
Order By: Relevance
“…The results achieved with this method are the current stateof-the-art on the NanoTWICE dataset, which we also use in our experiments. They improve upon previous results by Carrera et al (2017), who build a dictionary that yields a sparse representation of the normal data. Similar approaches using sparse representations for novelty detection are (Boracchi et al, 2014;Carrera et al, 2015Carrera et al, , 2016.…”
Section: Related Worksupporting
confidence: 75%
See 2 more Smart Citations
“…The results achieved with this method are the current stateof-the-art on the NanoTWICE dataset, which we also use in our experiments. They improve upon previous results by Carrera et al (2017), who build a dictionary that yields a sparse representation of the normal data. Similar approaches using sparse representations for novelty detection are (Boracchi et al, 2014;Carrera et al, 2015Carrera et al, , 2016.…”
Section: Related Worksupporting
confidence: 75%
“…Examples of defective and defect-free textures can be seen in Figure 4. We further evaluate our method on a dataset of nanofibrous materials (Carrera et al, 2017), which contains five defectfree gray-scale images of size 1024 × 700 for training and validation and 40 defective images for evaluation. A sample image of this dataset is shown in Figure 1…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…We singled out two of them as the most recent and powerful ones: the sparsity assumption and the self-similarity assumption. We found that two recent exponents use these assumptions to perform a sort of background subtraction: Carrera et al [21] for sparsity and Davy et al [33] for self-similarity.…”
Section: Discussionmentioning
confidence: 95%
“…As for the defect ratio y 1 , the algorithm proposed in Ref. was adopted. Briefly, the algorithm employs the sparse‐approximation technique for representing an image by using a limited number of significant patches, which are collected during a training phase performed on a set of images with no defects.…”
Section: Methodsmentioning
confidence: 99%